Penerapan Penilaian Portofolio Di SD Negeri Jati I Probolinggo - ., Ryzca Siti Qomariyah; ., Marizah Yulia Santoso; ., Nur Aulia Wijaya; Maulidia, Sabrina Dwi; ., Siti Romla (CV. ITTC INDONESIA, 2022)
At this time the assessment used in the independent curriculum is by applying portfolio assessment which is carried out at the end of the delivery of material, this portfolio assessment is proof that students have understood the learning material that has been conveyed. Portfolio Assessment is an assessment criterion in the form of practical results or learning outcomes that are given to students and related to the learning material that the teacher has conveyed in the form of collections of several questions. The sets of questions were self-made by the subject teachers who had taken them during the learning process and then the results of the portfolio assessment were stored in plastic folders in a systematic and coherent manner so that they were arranged according to the lesson plan given. This assessment is considered as an alternative assessment and is much more valid than the standard assessment. Portfolio assessment is not only used for assessment but also for research on student learning outcomes in terms of the skills and attitudes of students. The aspects measured in the portfolio assessment consist of three aspects, namely aspects of psychological development including cognitive, affective and psychomotor development. The function of portfolio assessment is to find out the level of understanding of the material students have been given, as a tool to find out the progress of students, to find out the learning difficulties of students in the learning process, and for the benefit of improving and perfecting teaching and learning activities (KMB). According to some researchers, this portfolio assessment is also a report to the parents of students so that they can find out about the progress of students while at school. From the results of observations and interviews that we have conducted at SD NEGERI 1 JATI CITY PROBOLINGGO, it can be concluded that portfolio assessment has been implemented in only a few classes, namely grade 1 and grade 4.